2010
DOI: 10.1590/s1984-82502010000300008
|View full text |Cite
|
Sign up to set email alerts
|

Central activities of hydroalcoholic extract from Lafoensia pacari A. St.-Hil. stem bark

Abstract: Lafoensia pacari A. St.-Hil. can be found from Amapá to Rio Grande do Sul states, and also in Paraguay and Bolivia. It is popularly known as pacari or mangava-brava and is used to promote weight loss, as an anti-thermal or tonic, to treat gastritis, ulcers, scarring, itching, discouragement, and cancer. In the open field tests, the hydroalcoholic extract from L. pacari stem bark (HEP) decreased the number of rearings, number of invaded squares, and increased immobility time compared to control animals. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…bergamia essential oil is involved with a noradrenergic component in the hypothalamic-pituitary-adrenal axis that reduce corticosterone levels [7]. While the S. odoratissima anxiolytic effect seems to be related to the serotonergic system, which may be mediated by 5-HT1A receptors since NAN-190 reversed the buspirone and the studied essential oil effects [56].…”
Section: Discussionmentioning
confidence: 95%
“…bergamia essential oil is involved with a noradrenergic component in the hypothalamic-pituitary-adrenal axis that reduce corticosterone levels [7]. While the S. odoratissima anxiolytic effect seems to be related to the serotonergic system, which may be mediated by 5-HT1A receptors since NAN-190 reversed the buspirone and the studied essential oil effects [56].…”
Section: Discussionmentioning
confidence: 95%
“…In the assessment of the antisecretory activity, three doses were initially chosen for LAF, based on Galdino et al (2010). LAF (75, 150, and 300 mg/kg) and ranitidine reduced the volume of gastric secretion by 9.64, 11.2, 15.66, and 9.24%, respectively, compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
“…However, several studies reported that various extracts from species of the family Lythraceae, such as Cuphea aequipetala (Avila et al, 2004), L. inermis (Borade et al, 2011) and Cuphea carthagensis (Elgindi et al, 2011), showed cytotoxicity. Galdino et al (2010) demonstrated the presence of saponins in fractions of L. pacari stem bark. Podolak et al (2010) reported that saponins possess cytotoxic activity, stimulate the apoptotic process, and cause cell cycle arrest and cytoskeleton disintegration in tumor cells.…”
Section: Discussionmentioning
confidence: 95%
“…Studies on the toxicity of L. pacari demonstrated that the stem bark extract from this plant was not toxic at a dose of 5 g/kg using a toxicity test in Wistar rats (Lago, 2004;Galdino et al, 2010) and in humans at the dose of 1.0 g/kg in a clinical trial for the eradication of Helicobacter pylori (da Mota et al, 2006). However, several studies reported that various extracts from species of the family Lythraceae, such as Cuphea aequipetala (Avila et al, 2004), L. inermis (Borade et al, 2011) and Cuphea carthagensis (Elgindi et al, 2011), showed cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%